2018
DOI: 10.4269/ajtmh.17-0739
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Severe Plasmodium vivax Malaria Mimicking Sepsis in a Neonate

Abstract: Severe congenital malaria associated with is uncommon. In Indonesia, most congenital malaria cases are due to infections. Most cases of congenital or neonatal malaria in endemic areas are diagnosed from peripheral smear as part of routine sepsis workup. Differentiating congenital and acquired neonatal malaria is very difficult. The case presented in this study describes severe malaria with cholestatic jaundice and sepsis-like signs and symptoms in neonates. The mother was asymptomatic and the neonate was succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Moreover, several researchers highlighted the diagnostic value of neonatal blood count [15], indexes of leukocyte and neutrophil concentrations [16], plasma fibronectin level in sepsis screens in neonates [17], the value of thrombocytopenia [18], platelet count [19], and the value of serum procalcitonin [20]. A recent diagnosis [21] described the clinical future of severe sepsis signs and symptoms among neonates in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several researchers highlighted the diagnostic value of neonatal blood count [15], indexes of leukocyte and neutrophil concentrations [16], plasma fibronectin level in sepsis screens in neonates [17], the value of thrombocytopenia [18], platelet count [19], and the value of serum procalcitonin [20]. A recent diagnosis [21] described the clinical future of severe sepsis signs and symptoms among neonates in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The low number of articles included in our search is alarming (n = 1, 5.8%) in view of the role of TLRs in P. vivax malaria. Although not often related to deaths, P. vivax is the most widely distributed Plasmodium species, being responsible for many cases of morbidity [ 1 , 4 ], and more recently also being described in cases of severe malaria [ 41 , 42 ]. This species also has epidemiological importance due to the characteristics of the parasite's biology that makes it difficult to interrupt the transmission cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Tatura et al showed that P. vivax infection in neonates presented with severe sepsis in endemic areas which was diagnosed by incidental findings of peripheral smear. 11 Severe anemia is the most common feature of P. falciparum malaria worldwide; however, in P. vivax-endemic areas, especially younger age group children are more prone for severe anemia with P. vivax infection. 2 The low parasite biomass burden of P. vivax indicates that due to rapid destruction of infected RBCs causing severe anemia and might be other pathophysiology plays adds on.…”
Section: Discussionmentioning
confidence: 99%